PEMBARUAN HUKUM DI BIDANG PERTANAHAN DAN IMPLEMENTASINYA TERHADAP OTONOMI DAERAH - Seto Cahyono (Perspektif, 2003)
The authority of animal husbandry arrangements in general should be arranged by the central government, therefore the regency/city government unnecessarily rule in general by using regency rules. It is for setting law certainty in the national law system while developing law especially for land affairs, whereas the Republic of Indonesia is still under one national defence law, that is, local law arrangement and technical practice.